A Set of Yellow Mustard (Sinapis alba L.) Germplasm with Polycotyledony - Yong-Bi Fu (Plants, 2023)
A world collection of 132 yellow mustard (Sinapis alba L.) accessions was characterized in a greenhouse to identify germplasm with polycotyledony and to assess the genetic segregation of tricot and tetracot seedlings in selfed S1 and S2 generations. The effort identified a set of 46 yellow mustard accessions with frequent occurrences of polycotyledony. The revealed genetic segregations seemed to suggest the development of tricot and tetracot seedlings in yellow mustard was largely controlled by a combination of genes at multiple diallelic loci. The identified tricot germplasm can be used to facilitate the genetic and/or genomic analysis of polycotyledonous germplasm for a better understanding of genetic and developmental mechanisms conditioning polycotyledony and the development of yellow mustard lines for explorable tricot breeding.